Arabidopsis AGAMOUS Regulates Sepal Senescence by Driving Jasmonate Production - Jibran, Rubina; Tahir, Jibran; Cooney, Janine; Hunter, Donald A.; Dijkwel, Paul P. (Frontiers in Plant Science, 2017)
The signal that initiates the age-regulated senescence programme in flowers is still unknown. Here we propose for the ephemeral Arabidopsis thaliana flower that it dies because of continued expression of the MADS-box transcription factor AGAMOUS (AG). AG is necessary for specifying the reproductive structures of the flower. Flowers of ag-1, which lack AG, exhibited delayed sepal senescence and abscission. The flowers also had reduced jasmonic acid (JA) content. Other anther-defective sterile mutants deficient in JA, defective in anther dehiscence 1 (dad1) and delayed dehiscence 2 (dde2), exhibited delayed sepal senescence and abscission as well. Manually pollinated dad1 flowers produced siliques but still had delayed senescence, demonstrating that absence of pollination does not cause delayed senescence. When ag-1, dad1 and dde2 flowers were sprayed with 100 µM methyl jasmonate, the sepal senescence and abscission phenotypes were rescued, suggesting that JA has a role in these processes. Our study uncovers a novel role for AG in determining the timing of death of the flower it helps develop and highlights a role for JA in sepal senescence.